2015
DOI: 10.1111/ijfs.12846
|View full text |Cite
|
Sign up to set email alerts
|

Modification of poovan banana (Musa AAB) starch by γ‐irradiation: effect on in vitro digestibility, molecular structure and physico‐chemical properties

Abstract: This study focussed at evaluating the effect of gamma irradiation on the in vitro digestibility, molecular structure and physico-chemical properties of poovan banana (Musa AAB) starch using c-rays from a 60 Co source at different doses with a dose rate of 2 kGy h À1 . Physico-chemical properties varied significantly and exhibited strong dose-dependent relationship. Escalating irradiation leads to decrease in amylose content, pH, swelling power of the starch granules and syneresis of the gelatinised starch, whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(2 citation statements)
references
References 38 publications
1
1
0
Order By: Relevance
“…This outcome coincides with the results of An et al (2017) who indicated that during storage, heme pigments of irradiated smoked duck meat increased with the exception of myoglobin. Our findings are in accordance with the results of (Reddy et al, 2015) who claimed that the Mb oxidized into MMb with the flow of time and raise of the dose level through an intermittent MbO2 process. A previous study investigated that the presence of antioxidants in meat samples moderately prevents myoglobin deterioration during processing, thus enabling good heme pigment value in meat samples (Cunha et al, 2018).…”
Section: Resultssupporting
confidence: 94%
“…This outcome coincides with the results of An et al (2017) who indicated that during storage, heme pigments of irradiated smoked duck meat increased with the exception of myoglobin. Our findings are in accordance with the results of (Reddy et al, 2015) who claimed that the Mb oxidized into MMb with the flow of time and raise of the dose level through an intermittent MbO2 process. A previous study investigated that the presence of antioxidants in meat samples moderately prevents myoglobin deterioration during processing, thus enabling good heme pigment value in meat samples (Cunha et al, 2018).…”
Section: Resultssupporting
confidence: 94%
“…Structural defects do manifest when AM chains pass through both the crystalline and amorphous layer (Genkina et al 2007) and if long AP chains are interspersed into the crystalline lamella (Koroteeva et al 2007). The dissimilarity in GTTs of legume starches is control by interplay of many factors such as size and shape of starch granules, degree of crystallinity, and molecular structure of starch and the ratio of AM to AP (Reddy et al 2015;Singh and Singh 2001). In a particular study, the GTTs (66.93, 83.71, and 91.82 C) of edible kudzu starches were higher than those reported for isolated starches from other botanical sources (Sukhija, Singh, and Riar 2017).…”
Section: Gelatinization Propertiesmentioning
confidence: 64%